Movement to Planting of Telang Flowers (Clitoria ternatea) in the Yards of The Employee Housing Housing House of PT. Gelora Mandiri Building Gane Barat - Melati, Rima; Syafi, Sartika; Arifin, Tuti Handayani; Suwarno, Kuad; Haryanto, Sugeng; Mandea, Abd. Rahmat; Suleyman, Suleyman (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2025)
Aiming to utilize empty land in the yard of the employee housing complex by planting butterfly pea flowers (Clitoria ternatea), at PT GMM, Gane Barat Selatan District, South Halmahera Regency which was implemented by the Agrotechnology Study Program, Faculty of Agriculture, Khairun University, Ternate through a participatory approach, this activity involved mothers in the employee housing complex to understand the benefits and techniques of planting butterfly pea flowers as medicinal ingredients, natural dyes and ornamental plants. The results and discussions showed that the movement to plant butterfly pea flowers in the yard of the employee housing complex was very much responded to by mothers in the PT GMM employee housing complex as part of an attractive and healthy greening of the environment, can reflect a sense of responsibility and concern for employees towards the surrounding environment and the spirit to support the company's program in terms of sustainability and nature conservation.